A new world-system : from chaos to sustainability - Reid, Donald G. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"A New World-System: From Chaos to Sustainability examines the present crisis in the social and ecological environment that is producing profound, potentially catastrophic challenges to the planet and humanity, and outlines a process for moving forward to address these critical issues. This book is a cautionary interpretation of the present, and vision for the future. Unlike other books on this or allied subjects that are singularly focused, Part 1 surveys the five major threats facing humanity today: climate change, inequality and poverty, new technologies, migration and globalization. It approaches the challenge of integrating these phenomena into a global picture from a systems perspective rather than taking a purely reductionist approach to understanding what is occurring in the world today. Part 2 moves from identifying the problems to solving them with chapters examining the ability of the present world-system to address these issues and outlining a process for action. The book concludes by discussing what could follow capitalism as a social organizing strategy and, perhaps more importantly, the consequences to the planet if we do not construct a new world-system. This book is essential reading for students and scholars of sustainable development, climate change, environmental studies, rural and urban planning, environmental psychology, political economy, sociology, social policy, leisure studies and environmental politics. More broadly, it is a vital resource for all those interested in building a sustainable society"--
OCLC-licensed vendor bibliographic record.
Keywords: Sustainability; Sustainable development; Climatic changes; Social change; NATURE / General; NATURE / Ecology; NATURE / Natural Resources